1994
DOI: 10.1161/01.str.25.4.759
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac prognosis of patients with carotid stenosis and no history of coronary artery disease. Veterans Affairs Cooperative Study Group 167.

Abstract: Patients with carotid stenosis have a high frequency of asymptomatic coronary artery disease (CAD). The purpose of this study of patients with asymptomatic carotid stenosis was to test the hypothesis that patients without a history of CAD have the same cardiac prognosis as patients with a history of CAD. Men enrolled in the Department of Veterans Affairs study on the efficacy of carotid endarterectomy for asymptomatic carotid stenosis underwent a baseline cardiac evaluation (history, physical examina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
5

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(39 citation statements)
references
References 39 publications
1
33
0
5
Order By: Relevance
“…Previous studies were based on exercise electrocardiograms or myocardial scintigraphy in patients with stroke or transient ischemic attack. [11][12][13][14][15][16][17][18][19][20][21][22] These small series suggested a prevalence of silent myocardial ischemia as high as 40%. In the present study, which, to our knowledge, is the largest ever using gold standard coronary angiography in nonfatal ischemic strokes, the 62% prevalence of coronary artery plaque and the 26% prevalence of coronary artery stenosis Ն50% was consistent with the 70% prevalence and 29% prevalence, respectively, found in a previous autopsy series of fatal stroke without coronary heart disease history.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies were based on exercise electrocardiograms or myocardial scintigraphy in patients with stroke or transient ischemic attack. [11][12][13][14][15][16][17][18][19][20][21][22] These small series suggested a prevalence of silent myocardial ischemia as high as 40%. In the present study, which, to our knowledge, is the largest ever using gold standard coronary angiography in nonfatal ischemic strokes, the 62% prevalence of coronary artery plaque and the 26% prevalence of coronary artery stenosis Ն50% was consistent with the 70% prevalence and 29% prevalence, respectively, found in a previous autopsy series of fatal stroke without coronary heart disease history.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective analyses of large CE series, including recent randomized trials, have consistently demonstrated a statistically significant association between preoperative history of CHD and surgical risk, including operative mortality and early and late postoperative cardiac morbidity. [75][76][77][78][79] In a study of 22 165 cases randomly selected from Medicare beneficiaries undergoing CE between 1988 and 1990 and followed up through 1992, there was a significant correlation between preoperative history of acute myocardial ischemia and CHF and perioperative death and stroke, as well as longer-term postoperative survival. 80 Several studies have assessed the prevalence of asymptomatic or clinically silent CHD by using consistent protocols of preoperative screening and have correlated silent CHD with postoperative mortality and cardiac morbidity after CE.…”
Section: In the Setting Of Cementioning
confidence: 99%
“…83 In the Veterans Affairs trial of CE for asymptomatic disease, a subgroup of patients without overt history of CHD but with other associated atherosclerotic vascular risk factors had a high perioperative risk of cardiac events similar to that of patients with symptomatic CHD. 75 No study with adequate statistical power has shown absence of association with CHD, including clinically silent disease, with morbidity after CE. Paradoxically, a recent analysis of surgical complications in the North American Symptomatic Carotid Endarterectomy Trial (NASCET) re- Intensify LDL-lowering therapy (statin or resin*).…”
Section: In the Setting Of Cementioning
confidence: 99%
“…20 With her negative transcranial Doppler embolus detection results, she will be at lower risk of stroke with medical therapy than with stenting or endarterectomy. So would 90% of patients with asymptomatic carotid stenosis.…”
Section: The Patientmentioning
confidence: 99%